Plan de negocios para la elaboración y comercialización de un whisky ecuatoriano con canela ceilán de alta calidad importada de Sri Lanka - Díaz Guerrero, Kevin Sebastián (2018)
This business plan is focused on demonstrating the feasibility of implementing and setting up a company dedicated to the production and marketing of an Ecuadorian whiskey flavored with cinnamon, in the cities of Quito, Ambato and Riobamba, which, in its production, will have a differentiation in imported raw material from Sri Lanka. To begin with, a thorough investigation of the environment was carried out, which produced apparently favorable data regarding the growth of the alcoholic beverages sector, the consumption that currently exists within the country and various economic indicators such as inflation, country risk, and others that must be analyzed prior to the implementation of any business. Then, tastes and preferences of the possible consumers were identified through market research, which included interviews with experts. These interviews were a source of information and relevant recommendations that allowed good decision-making in aspects of marketing, sales force, advertising and production. Additionally, the target market was obtained through geographic, demographic and behavioral segmentation, which resulted in Ecuadorian men and women located in the cities of Quito, Ambato and Riobamba, who are between 18 and 35 years old, belonging to socioeconomic levels (A, B, C +) and that have liquor consumption as their behavior. Finally, a financial plan was carried out in which it was determined that the initial investment required will be USD 26,970 financed in full by capital contributions from the 3 partners. The financial indicators also showed positive data that confirmed the viability of the project, with a VAN of USD 19,570, TIR of 38% and a recovery period of 2 years 8 months.